RELI: Optimalisasi Kemampuan Literasi Siswa Kelas IV–VI melalui Teknik Retelling di SDN 2 Demulih - Ni Nyoman Sandat; Luh Made Dwi Wedayanthi (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Literacy skills in elementary schools play a crucial role in supporting students’ academic development and overall learning success. However, observations conducted at SDN 2 Demulih revealed that many students still experience difficulties in comprehending reading materials and retelling stories coherently and systematically. This study aims to enhance students’ literacy and language skills through the implementation of the retelling technique as an instructional strategy. A descriptive research approach employing the ADDIE development model was applied, consisting of five stages: analysis, design, development, implementation, and evaluation. The program involved 21 students from grades IV–VI and utilized two audiovisual story media, namely “Independence” and “Bawang dan Kesuna.” The results indicate that the application of the retelling technique based on audiovisual media effectively improved students’ reading comprehension, learning activeness, and self-confidence in speaking activities. Students were able to reconstruct storylines accurately and express moral messages using their own words. Therefore, the retelling technique is proven to be an engaging, practical, and effective literacy learning strategy for elementary school students.